"Endothelium-Out" and "Endothelium-In" descemet membrane endothelial keratoplasty (DMEK) graft insertion techniques: a systematic review with meta-analysis - Ong, Hon Shing (2022)
Background: We evaluated the visual outcomes and complications of “endothelium-out” and “endothelium-in” Descemet membrane endothelial keratoplasty (DMEK) graft insertion techniques. Materials and Methods: Electronic searches were conducted in CENTRAL, Cochrane databases, PubMed, EMBASE, ClinicalTrials.gov. Study designs included clinical trials, comparative observational studies, and large case series (≥25 eyes). PRISMA guidelines were used for abstracting data and synthesis. Random-effects models were employed for meta-analyses. Results: 21,323 eyes (95 studies) were included. Eighty-six studies reported on “endothelium-out” techniques; eight studies reported on “endothelium-in” techniques. One study compared “endothelium-out” to “endothelium-in” techniques. Eighteen “endothelium-out” studies reported that 42.5–85% of eyes achieved best-corrected visual acuity (BCVA) ≥20/25 at 6 months; pooled proportion of eyes achieving BCVA ≥20/25 at 6 months was 58.7% (95% CI 49.4–67.7%,15 studies). Three “endothelium-in” studies reported that 44.7–87.5% of eyes achieved BCVA of ≥20/25 at 6 months; pooled proportion of eyes achieving BCVA ≥20/25 at 6 months was 62.4% (95% CI 33.9–86.9%). Pooled mean endothelial cell loss was lower in the “endothelium-in” studies (28.1 ± 1.3%, 7 studies) compared to “endothelium-out” studies (36.3 ± 6.9%,10 studies) at 6 months (p = 0.018). Graft re-bubbling rates were higher in the “endothelium-out” studies (26.2%, 95% CI 21.9–30.9%, 74 studies) compared to “endothelium-in” studies (16.5%, 95% CI 8.5–26.4%, 6 studies), although statistical significance was not reached (p = 0.440). Primary graft failure rates were comparable between the two groups (p = 0.552). Quality of evidence was considered low and significant heterogeneity existed amongst the studies. Conclusion: Reported rates of endothelial cell loss were lower in “endothelium-in” DMEK studies at 6 months compared to “endothelium-out” studies. Outcomes of “endothelium-in” techniques were otherwise comparable to those reported in “endothelium-out” studies. Given the technical challenges encountered in “endothelium-out” procedures, surgeons may consider “endothelium-in” techniques designed for easier intra-operative DMEK graft unfolding. “Endothelium-in” studies evaluating outcomes at longer time points are required before conclusive comparisons between the two techniques can be drawn.